1995
DOI: 10.1002/1097-0142(19951115)76:10<1737::aid-cncr2820761010>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of small hepatocellular carcinoma with percutaneous ethanol injection. Analysis of prognostic factors in 105 western patients

Abstract: Background. Percutaneous ethanol injection (PEI) has been used in the Far East for treating small, unresectable hepatocellular carcinoma (HCC). To clarify when treatment with PEI may be best indicated for Western patients with HCC, the authors performed a retrospective analysis of the clinicopathologic factors influencing prognosis. Methods. From December 1987 to August 1994, 105 patients with cirrhosis with HCC received PEI as the sole anticancer treatment. Eighty‐two patients had uninodular tumors smaller th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
94
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(104 citation statements)
references
References 44 publications
8
94
1
1
Order By: Relevance
“…A threshold AFP value of 200 ng/mL is used based on its specificity of 90%. [34][35][36]38,44 The sensitivity of AFP level at this value ranges between 40% and 60%. [34][35][36]38,44 The sensitivity of U/S in detecting HCC ranges from 55% to 85%.…”
Section: Screening Sensitivity and Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…A threshold AFP value of 200 ng/mL is used based on its specificity of 90%. [34][35][36]38,44 The sensitivity of AFP level at this value ranges between 40% and 60%. [34][35][36]38,44 The sensitivity of U/S in detecting HCC ranges from 55% to 85%.…”
Section: Screening Sensitivity and Specificitymentioning
confidence: 99%
“…[34][35][36]38,44 The sensitivity of AFP level at this value ranges between 40% and 60%. [34][35][36]38,44 The sensitivity of U/S in detecting HCC ranges from 55% to 85%. 34,[45][46][47][48][49]50 U/S has specificity between 90% and 94% in detecting HCC.…”
Section: Screening Sensitivity and Specificitymentioning
confidence: 99%
“…Specifically, one category is that of image-guided tumor ablation therapies, which includes chemical ablation (mainly with the percutaneous ethanol injection), and thermal ablation, which can be either hyperthermic, such as radiofrequency ablation (RFA), microwave ablation (MWA) and laser ablation, or cryoablation. [44][45][46][47][48] Treatment with percutaneous alcohol injection involves several sessions under the guidance of ultrasound, and although there are no randomized controlled trials, it has been shown to improve the natural history of HCC. 44 Radiofrequency ablation, by causing thermal injury to the tissue through electromagnetic energy deposition, has been shown to offer a survival advantage either alone or in combination with resection.…”
Section: Technologic Innovationsmentioning
confidence: 99%
“…[44][45][46][47][48] Treatment with percutaneous alcohol injection involves several sessions under the guidance of ultrasound, and although there are no randomized controlled trials, it has been shown to improve the natural history of HCC. 44 Radiofrequency ablation, by causing thermal injury to the tissue through electromagnetic energy deposition, has been shown to offer a survival advantage either alone or in combination with resection. 45 What is becoming increasingly interesting are the findings that RFA may actually have similar effect to resection as a first-line treatment in patients with early-stage cirrhosis and single lesions ,5 cm.…”
Section: Technologic Innovationsmentioning
confidence: 99%
“…6,7 Nevertheless, repetitive treatment with close follow-up can achieve a long-term tumoricidal effect. [8][9][10] There has been only limited experience with microwave ablation and this has mainly been in Japan. It has been used for more than a decade as an effective method to achieve long-term control of HCC.…”
mentioning
confidence: 95%